2021
DOI: 10.1038/s41598-021-96472-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green-manure and tillage management on soil microbial community composition, nutrients and tree growth in a walnut orchard

Abstract: This study characterized the effect of green manures (February orchid, hairy vetch, rattail fescue and a no-green-manure control) and the termination method (flail or disk) on nutrient contents, enzyme activities, microbial biomass, microbial community structure of rhizosphere soil and vegetative growth of walnut tree. All three selected green manures significantly enhanced the water content, organic C, total N and available P. The rattail fescue significantly decreased the mineral N. Total organic C, total N,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 43 publications
(58 reference statements)
0
16
0
1
Order By: Relevance
“…The decomposition of green manure will affect the soil nutrients, and the latter will affect the structural diversity and abundance of the soil microbial community [5,6,18]. Microorganisms are the main driving force of the soil nutrient material cycle, and the microbial communities in the soil are vulnerable to the influence of the external environment; thus, they react to the soil environment [37,38].…”
Section: Correlation Between Soil Nutrients Microbial Composition and The Plant Decomposition Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…The decomposition of green manure will affect the soil nutrients, and the latter will affect the structural diversity and abundance of the soil microbial community [5,6,18]. Microorganisms are the main driving force of the soil nutrient material cycle, and the microbial communities in the soil are vulnerable to the influence of the external environment; thus, they react to the soil environment [37,38].…”
Section: Correlation Between Soil Nutrients Microbial Composition and The Plant Decomposition Indexmentioning
confidence: 99%
“…In parallel with the rapid development of modern industry, the unreasonable application of chemical fertilizer has caused a series of environmental and safety problems [1][2][3], which deters the realization of the target for sustainable development [3]. Planting green fertilizer can reduce the use of chemical fertilizers and pesticides [4], and the use of green manure can increase the contents of soil nutrients and improve the soil fertility and structure of soil microbial community among others [5,6]. It is of substantial significance to cultivate high-quality green manure varieties and develop the green manure industry for the ecological environment and agricultural green sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Asagi and Ueno (2009) found that T. repens L. and Vicia villosa Roth were the most efficient N sources for rice yield. It was previously reported that the benefits associated with weed control, water holding capacity, rhizosphere soil ecology, and soil conservation might be attributed to V. villosa (Dong et al, 2021;Choi and Daimon, 2008;Hartwig and Ammon, 2002). Thus, the green manure improves soil conditions, nutrient availability and cycling, and soil physical properties (Ma et al, 2021;Karkanis et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Using green cover crops as plant fertility is an effective environmental protection measure to improve fruit quality and decrease fertiliser consumption ( Srivastava et al., 2007 ; Chen et al., 2014 ; Dong et al., 2021 ). Meanwhile, some scholars have studied the effects of green manures on pear orchards.…”
Section: Introductionmentioning
confidence: 99%